Sistema de información para la gestión de eventos, recursos y traslados en las ambulancias de la Cruz Roja Colombiana Seccional Cundinamarca Bogotá - Miranda Molina, Diana Carolina; Gamba Roncancio, Yheison Javier (Universidad Antonio Nariño, 2021)
In the Colombian Red Cross Sectional Cundinamarca Bogotá the Extra Mural process performs the management of ambulance transfers, from a SAMU or IPS to the place authorized by the healthcare provider of the patient who needs this service